Description of Neochlorella semenenkoi gen. et. sp. nov. (Chlorophyta, Trebouxiophyceae), a Novel Chlorella-like Alga with High Biotechnological Potential - Krivina, Elena S.; Bobrovnikova, Lidia A.; Temraleeva, Anna D.; Markelova, Alexandra G.; Gabrielyan, David A.; Sinetova, Maria A. (Diversity (Basel), 2023)
Despite many publications about Chlorella-like algae, their reliable and accurate identification is still difficult due to their simplicity and high phenotypic plasticity. The molecular approach has revolutionized our understanding of the diversity of ’small green balls’, and a natural classification of this group is currently being developed. This work is aimed at providing a detailed study of the phylogenetic position, morphology, ultrastructure, and physiology of the biotechnologically remarkable Chlorella-like strain IPPAS C-1210. Based on the SSU–ITS1–5.8S–ITS2 phylogeny, genetic distances, and the presence of compensatory base changes (CBCs) in ITS1 and conserved regions of ITS2 secondary structures, we describe a new genus, Neochlorella, with IPPAS C-1210 as the authentic strain of the type species, N. semenenkoi gen. and sp. nov. In addition, we justify the reassignment of the strain C. thermophila ITBB HTA 1–65 into N. thermophila comb. nov. The distinctive ultrastructural and physiological traits of the new species are discussed.